PERSONNEL TRAINING FOR THE CONSTRUCTION INDUSTRY OF THE REGION - Azamat I. Al’Bakasov; Viktoriya A. Gur’Yeva (Высшее образование в России, 2016)
The article substantiates the need to increase the efficiency of interaction of higher education institution with employers for solution of the problem of training high-quality personnel. The authors show the role of practical work in development of students’professional competences and skills.